Growth Performance of Crossbred Calves Fed Total Mixed Ration with Moringa Oleifera Leaves - Sharma, Meet M; Lunagariya, Pravin M; Trivedi, Pankaj G; Shah, Preet H; Sorathiya, Kalpesh K; Patel, Ashish C; Wadhwani, Kishan N (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The experiment was designed to study the effect of Moringa oleifera leaves inclusion in total mixed ration on 50% protein base  replacement of calf starter on growth, feed intake, digestibility, feed efficiency, and cost of feeding in crossbred calves. The fourteen  newborn crossbred calves (75% HF x 25% Kankrej) were sequentially allocated to control (T1) and study (T2) groups. The calves were  fed using calf starter and 50% calf starter replaced with M. oleifera leaves (MOL, both had equivalent protein %), in T1 and T2 group,  respectively. Both TMR were having roughage to concentrate ratio 75:25 and 65:35 during 1-14 and 14-18 weeks of age, respectively.  The gain in body weight and body measurements like heart girth, body length was similar in both treatments, except wither height,  which was lower in T2 group. The intake of dry matter, crude protein, ether extract, nitrogen free extract, metabolizable energy and  water (daily, percent and metabolic body weight basis) was statistically similar in both groups, except percent intake of crude protein,  metabolizable energy and energy intake on metabolic body weight which was lower in T2 group. The digestibility of nutrients, and  feed conversion efficiency were statistically similar in both groups. The cost of feeding for weight gain was 6.26% higher in 50% MOL  inclusion T2 group than the control T1 group.
Keywords: Crossbred calves; Digestibility; Feed efficiency; Feeding cost; Growth; Intake; M.oleifera leaves